Negotiations and diplomatic protocol as a mean of political conflicts resolution - SIEKUNOVA, IULIIA (Journal of Education, Technology and Computer Science, 2016)
The author of the article made an attempt to prove the relevance and importance of such topic as negotiations and diplomatic protocol as a mean of conflicts resolution. Bases of negotiations were determined; etymology of word “protocol”, the role and importance of diplomatic protocol for the development of modern international politics was described.